2004
DOI: 10.1097/01.fjc.0000166309.63808.5f
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of a Selective Endothelin-A Receptor Antagonist YM598 on Endothelin-1-induced Potentiation of Nociception in Formalin-induced and Prostate Cancer-induced Pain Models in Mice

Abstract: In some diseases in which endothelin-1 (ET-1) production increases (e.g. prostate cancer), ET-1 is considered to be involved in the generation of pain. In the present study, we investigated the effects of a selective endothelin-A receptor antagonist, YM598, on the nociception potentiated by ET-1 in formalin-induced and cancer inoculation-induced pain models in mice. The formalin-induced pain model was prepared by intraplantar injection of 0.7% formalin into the hind paws of ICR mice, and the cancer pain model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Pain is prevalent in about 70% of people with metastatic cancers such as prostate and breast cancer 97. Exogenous application of ET-1 in animal models of cancer has been found to potentiate cancer-induced nociception and sensitization of C-fibers to heat via activation of ET A receptors, a similar pathway as that seen in ET-1-induced potentiation of formalin- and capsaicin-induced nociception 98,99. It has been shown that the concentration of ET-1 has a more direct correlation to pain levels than the size of the tumor in mice,100 illustrating the importance of evaluating algogens released by cancerous tumors, such as ET-1, to identify novel therapeutic targets to treat cancer pain.…”
Section: Specific Diseasesmentioning
confidence: 89%
“…Pain is prevalent in about 70% of people with metastatic cancers such as prostate and breast cancer 97. Exogenous application of ET-1 in animal models of cancer has been found to potentiate cancer-induced nociception and sensitization of C-fibers to heat via activation of ET A receptors, a similar pathway as that seen in ET-1-induced potentiation of formalin- and capsaicin-induced nociception 98,99. It has been shown that the concentration of ET-1 has a more direct correlation to pain levels than the size of the tumor in mice,100 illustrating the importance of evaluating algogens released by cancerous tumors, such as ET-1, to identify novel therapeutic targets to treat cancer pain.…”
Section: Specific Diseasesmentioning
confidence: 89%
“…17-19 For example, endothelin (ET-1), a vasoactive peptide that is produced by a number of different malignancies, sensitizes peripheral afferent sensory nerve fibers and contributes to both soft tissue and bone cancer pain as well as pain due to oral squamous cell carcinoma. 7,16,19,20 We recently demonstrated that the site of action for ET-1 in producing cancer pain in a mouse model is in the periphery within the tumor microenvironment. 19 The finding that a peripheral nociceptive mediator is responsible for cancer pain supports our current finding in humans that surgical resection leads to a significant reduction in pain since the cellular source of the mediator would be removed.…”
Section: Discussionmentioning
confidence: 99%
“…ET-1 enhances pain states in various models of acute chemicaland inflammation-induced pain and in chronic pain types such as neuropathic pain, where selective ET A inhibition shows preclinical efficacy (26). The key relevance of ET-1 and the effectiveness of ET A inhibition have also been shown in acute pain models, both irritant induced and prostate cancer related (27). In the latter experiments, ET-1 axis inhibition both with small-molecule inhibitors resulted in significant pain control.…”
Section: Ets and Their Receptorsmentioning
confidence: 92%